Integrated structural, thermal, and electrochemical analysis of gold-modified activated carbon–polyurethane electrodes - Muhammad Abdurrahman, Munir; Fitria, Rahmawati; David, Fernando; Imam Shofid, Alaih; Ahlam, Inayatullah; Abdul, Rohman (Malaysian Analytical Sciences Society (ANALIS), 2026)
This study presents the development and comprehensive characterization of bio-based polyurethane (PU) composites reinforced with gold (Au) nanoparticles for multifunctional performance enhancement. The PU matrix was synthesized using methylene diphenyl diisocyanate (MDI) and palm kernel oil-derived polyol, while Au nanoparticles were incorporated at varying loadings (1, 2, 5, and 10 wt%) via a sonication-assisted solution casting technique. Fourier Transform Infrared Spectroscopy (FTIR) confirmed the structural integrity of the PU backbone and suggested non-covalent interactions, such as hydrogen bonding, between Au and polar groups in the matrix. Principal Component Analysis (PCA) of FTIR data further distinguished composite formulations based on spectral variations, highlighting the influence of Au at the molecular level. Field Emission Scanning Electron Microscopy (FESEM) revealed uniform dispersion of Au with minimal aggregation, supporting strong matrix-filler interaction. Thermogravimetric Analysis (TGA) and Differential Scanning Calorimetry (DSC) showed satisfactory thermal stability, delayed degradation, and increased char residue, especially at 5–10 wt% Au, attributed to Au’s high thermal conductivity and barrier effect. Electrochemical Impedance Spectroscopy (EIS) revealed that increasing the Au content reduces the resistance value, suggesting the creation of efficient conductive pathways.